Using TRIS-Buffered Plasma-Activated Water to Reduce Pathogenic Microorganisms on Poultry Carcasses with Evaluation of Physicochemical and Sensory Parameters - Vanessa Große-Peclum; Lisa Siekmann; Carsten Krischek; Georg Avramidis; Christian Ochs; Wolfgang Viöl; Madeleine Plötz (Foods, 2023)
Foodborne diseases are mainly caused by the contamination of meat or meat products with pathogenic microorganisms. In this study, we first investigated the in vitro application of TRIS-buffered plasma-activated water (Tb-PAW) on Campylobacter (C.) jejuni and Escherichia (E.) coli, with a reduction of approx. 4.20 ± 0.68 and 5.12 ± 0.46 log10 CFU/mL. Furthermore, chicken and duck thighs (inoculated with C. jejuni or E. coli) and breasts (with natural microflora) with skin were sprayed with Tb-PAW. Samples were packed under a modified atmosphere and stored at 4 °C for 0, 7, and 14 days. The Tb-PAW could reduce C. jejuni on days 7 and 14 (chicken) and E. coli on day 14 (duck) significantly. In chicken, there were no significant differences in sensory, pH-value, color, and antioxidant activity, but %OxyMb levels decreased, whereas %MetMb and %DeoMb increased. In duck, we observed slight differences in pH-value, color, and myoglobin redox forms for the Tb-PAW, which were not perceived by the sensory test persons. With only slight differences in product quality, its application as a spray treatment may be a useful method to reduce C. jejuni and E. coli on chicken and duck carcasses.